Functional Variants in DPYSL2 Sequence Increase Risk of Schizophrenia and Suggest a Link to mTOR Signaling. Issue 1 (1st January 2015) - Liu, Yaping; Pham, Xuan; Zhang, Lilei; Chen, Pei-lung; Burzynski, Grzegorz; McGaughey, David M; He, Shan; McGrath, John A; Wolyniec, Paula; Fallin, Margaret D; Pierce, Megan S; McCallion, Andrew S; et al.
Abstract: Numerous linkage and association studies by our group and others have implicated DPYSL2 at 8p21.2 in schizophrenia. Here we explore DPYSL2 for functional variation that underlies these associations. We sequenced all 14 exons of DPYSL2 as well as 27 conserved noncoding regions at the locus in 137 cases and 151 controls. We identified 120 variants, eight of which we genotyped in an additional 729 cases and 1542 controls. Several were significantly associated with schizophrenia, including a three single-nucleotide polymorphism (SNP) haplotype in the proximal promoter, two SNPs in intron 1, and a polymorphic dinucleotide repeat in the 5′-untranslated region that alters sequences predicted to be involved in translational regulation by mammalian target of rapamycin signaling. The 3-SNP promoter haplotype and the sequence surrounding one of the intron 1 SNPs direct tissue-specific expression in the nervous systems of Zebrafish in a pattern consistent with the two endogenous dpysl2 paralogs. In addition, two SNP haplotypes over the coding exons and 3′ end of DPYSL2 showed association with opposing sex-specific risks. These data suggest that these polymorphic, schizophrenia-associated sequences function as regulatory elements for DPYSL2 expression. In transient transfection assays, the high risk allele of the polymorphic dinucleotide repeat diminished reporter expression by 3- to 4-fold. Both the high- and low-risk alleles respond to allosteric mTOR inhibition by rapamycin until, at high drug levels, allelic differences are eliminated. Our results suggest that reduced transcription and mTOR-regulated translation of certain DPYSL2 isoforms increase the risk for schizophrenia.